Peran Perceived Value Dalam Memoderasi Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan Kuliner Kota Barat Solo - Rohwiyati Rohwiyati; Praptiestrini Praptiestrini (Universitas Tidar, 2020)
Competition in the culinary business in the city of Solo is currently very tight, and critical consumer demands are an important problem for entrepreneurs to always provide high satisfaction to customers. Service quality is not enough to satisfy customers, but it needs to be high value for customers. This study aims to analyze (1) effect service quality and perceived value on customer satisfaction; (2) effect perceived value on customer satisfaction; (3) effect service quality on customer satisfaction moderated of perceived value. This research using sample 100 customers who buy culinary in Kota Barat Solo Area. Data collecting with questionaire technique through validity and reliability test. The data analyse using regression linear analysis and absolute residual test, and previously the researcher using classical assumption test. Results of this research showed that (1) service quality have a significantly effect on customer satisfaction; (2) perceived value have a significantly effect on customer satisfaction; (3) perceived value has moderate the effect of service quality on customer satisfaction.